An identified serotonergic neuron regulates adult neurogenesis in the crustacean brain - Sandeman, D.C. (2009)
New neurons are born and integrated into functional circuits in the brains of many adult organisms. In virtually all of these systems, serotonin is a potent regulator of neuronal proliferation. Specific neural pathways underlying these serotonergic influences have not, however, been identified and manipulated. The goal of the present study was to test whether adult neurogenesis in the crustacean brain is influenced by electrical activity in the serotonergic dorsal giant neurons (DGNs) innervating the primary olfactory processing areas, the olfactory lobes (OLs), and higher order centers, the accessory lobes (ALs). Adult-born neurons occur in two interneuronal cell clusters that are part of the olfactory pathway. The present study demonstrates that neurogenesis also continues in these areas in a dissected, perfused brain preparation, although the rate of neuronal production is lower than in brains from intact same-sized animals. Inclusion of 10(−9)M serotonin in the perfusate delivered to the dissected brain preparation restores the rate of neurogenesis to in vivo levels. While subthreshold stimulation of the DGN does not significantly alter the rate of neurogenesis, electrical activation of a single DGN results in significant increases in neurogenesis in Cluster 10 (CL10) on the same side of the brain, compared with levels on the contralateral, unstimulated side. Measurements of serotonin levels in the perfusate using high performance liquid chromatography established that serotonin levels are elevated about ten-fold during DGN stimulation, confirming that serotonin is released during DGN activity. This is the first identified neural pathway through which adult neurogenesis has been directly manipulated.